Peningkatan Kompetensi Guru Madrasah Melalui Pendekatan TPACK dan PLC untuk Menghadapi Tantangan Pendidikan Islam - Dwi Noviani; Hilmin Hilmin; Choiriyah Choiriyah; Khozin Khozin; Firdaus Basuni (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
Islamic education has a strategic role in shaping the character, morality, and spirituality of students, but it is faced with complex challenges in the era of social, cultural, and technological transformation. The low pedagogic and professional competence of some teachers, the limitations of digital literacy, the dominance of conventional learning methods, and a less contextual curriculum are significant obstacles. This service program is designed to improve the competence of madrasah teachers through participatory training approaches, intensive mentoring, and strengthening learning communities based on the concepts of Technological Pedagogical Content Knowledge (TPACK) and Professional Learning Community (PLC). Activities include initial assessments, competency workshops, the use of learning technology, weekly mentoring, and pre-test and post-test evaluations. The results showed a significant increase in pedagogic competence (28%) and mastery of technology (34%), accompanied by positive changes in motivation, innovative attitudes, and awareness of contextualization of teaching materials. However, time constraints, variations in digital literacy, and institutional support are obstacles that need to be overcome through synergy between stakeholders. These findings underscore the importance of continuous, reflective, and contextual coaching models to strengthen the role of teachers as agents of change in Islamic education.